Benefit from the Chin-Down Maneuver in the Swallowing Performance and Self-Perception of Parkinson’s Disease Patients - Annelise Ayres; Geraldo Pereira Jotz; Carlos R. M. Rieder; Maira Rozenfeld Olchik (Parkinson's Disease)
Aims. To verify the effectiveness of the maneuver application in swallowing therapy with PD. Materials and Method. We performed an open-label trial, with three groups compounds by PD individuals: the experimental group, control group, and orientation group. The study included PD patients with dysphagia. A cognitive screening, through a questionnaire about depression and quality of life, was conducted. Swallowing assessment was performed through (1) fiberoptic endoscopic evaluation of swallowing (FEES); (2) clinical evaluation and Functional Oral Intake Scale (FOIS); and (3) assessment of the quality life related to swallowing (SWALQOL). A therapeutic program, which consisted of chin-down postural maneuver and orientations on feeding, was applied. Both groups (EG and OG) received on-month therapeutic program. Results. A significant improvement in swallowing, evaluated by clinical assessment, was observed in solid (p<0.001) and liquid (p=0.022) consistencies in EG when compared to OG and CG. Patients in EG presented improvement in QoL, with the significant difference in comparison with the other groups, about domain frequency of symptoms (p=0.029) in SWALQOL questionnaire. Conclusion. The postural maneuver chin-down improved swallowing performance and self-perception, but not the laryngeal signs. This trial is registered with registration number NCT02973698.